Perfusion Computed Tomography at Posttraumatic Cerebral Fat Embolism - Alex Trofi mov; George Kalentyev; Michail Yuryev; Alevtina Ruzavina; Kristina Ksenofontova; Michael Karelsky (Open Journal of Trauma - Peertechz Publications, 2017)
The article reports a clinical case illustrating favorable outcome of nonsurgical treatment of a  polytraumazed patient with occult severe cerebral fat embolism. The peculiar characteristics of the  perfusion CT are demonstrated.